Endothelial cell-specific roles for tetrahydrobiopterin in myocardial function, cardiac hypertrophy, and response to myocardial ischemia-reperfusion injury - Chuaiphichai, S; Chu, SM; Carnicer, R; Kelly, M; Bendall, JK; Simon, JN; Douglas, G; Crabtree, MJ; Casadei, B; Channon, KM (American Physiological Society, 2023)
The cofactor tetrahydrobiopterin (BH4) is a critical regulator of nitric oxide synthase (NOS) function and redox signaling, with reduced BH4 implicated in multiple cardiovascular disease states. In the myocardium, augmentation of BH4 levels can impact on cardiomyocyte function, preventing hypertrophy and heart failure. However, the specific role of endothelial cell BH4 biosynthesis in the coronary circulation and its role in cardiac function and the response to ischemia has yet to be elucidated. Endothelial cell-specific Gch1 knockout mice were generated by crossing Gch1fl/fl with Tie2cre mice, generating Gch1fl/flTie2cre mice and littermate controls. GTP cyclohydrolase protein and BH4 levels were reduced in heart tissues from Gch1fl/flTie2cre mice, localized to endothelial cells, with normal cardiomyocyte BH4. Deficiency in coronary endothelial cell BH4 led to NOS uncoupling, decreased NO bioactivity, and increased superoxide and hydrogen peroxide productions in the hearts of Gch1fl/flTie2cre mice. Under physiological conditions, loss of endothelial cell-specific BH4 led to mild cardiac hypertrophy in Gch1fl/flTie2cre hearts. Endothelial cell BH4 loss was also associated with increased neuronal NOS protein, loss of endothelial NOS protein, and increased phospholamban phosphorylation at serine-17 in cardiomyocytes. Loss of cardiac endothelial cell BH4 led to coronary vascular dysfunction, reduced functional recovery, and increased myocardial infarct size following ischemia-reperfusion injury. Taken together, these studies reveal a specific role for endothelial cell Gch1/BH4 biosynthesis in cardiac function and the response to cardiac ischemia-reperfusion injury. Targeting endothelial cell Gch1 and BH4 biosynthesis may provide a novel therapeutic target for the prevention and treatment of cardiac dysfunction and ischemia-reperfusion injury. NEW & NOTEWORTHY We demonstrate a critical role for endothelial cell Gch1/BH4 biosynthesis in coronary vascular function and cardiac function. Loss of cardiac endothelial cell BH4 leads to coronary vascular dysfunction, reduced functional recovery, and increased myocardial infarct size following ischemia/reperfusion injury. Targeting endothelial cell Gch1 and BH4 biosynthesis may provide a novel therapeutic target for the prevention and treatment of cardiac dysfunction, ischemia injury, and heart failure.